Answer:
x =
±
![(√(13) )/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ym7oke3jsd4j4ulycvvrw9knf4lmwzvc49.png)
Explanation:
Given
x² - 7x + 9 = 0 ( subtract 9 from both sides )
x² - 7x = - 9
Solve using the method of completing the square
add ( half the coefficient of the x- term)² to both sides
x² + 2( -
)x +
= - 9 +
(x -
)² =
( take the square root of both sides )
x -
= ±
= ±
( add
x =
±
=
![(7+/-√(13) )/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/obqluyjpfiahzwr9sbs8yvek2ydogztyvo.png)